Cytotoxicity and genotoxicity of CuO nanoparticles in sea urchin spermatozoa through oxidative stress. (September 2018) - Gallo, Alessandra; Manfra, Loredana; Boni, Raffaele; Rotini, Alice; Migliore, Luciana; Tosti, Elisabetta
Abstract: Copper oxide nanoparticles (CuO NPs) are extensively used in various industrial and commercial applications. Despite their wide application may lead to the contamination of marine ecosystem, their potential environmental effects remain to be determined. Toxicity assessment studies have primarily focused on investigating the effects of CuO NPs on fertilization success and embryo development of different sea urchin species while the impact on sperm quality have never been assessed. In this line, this study aims to assess the effects of CuO NPs on the spermatozoa of the sea urchin Paracentrotus lividus . After sperm exposure to CuO NPs, biomarkers of sperm viability, cytotoxicity, oxidative stress, and genotoxicity as well as morphology were evaluated. Results showed that CuO NPs exposure decreased sperm viability, impaired mitochondrial activity and increased the production of reactive oxygen species (ROS) and lipid peroxidation. Furthermore, CuO NPs exposure caused DNA damage and morphological alterations. Together with the antioxidant rescue experiments, these results suggest that oxidative stress is the main driver of CuO NP spermiotoxic effects. The mechanism of toxicity is here proposed: the spontaneous generation of ROS induced by CuO NPs and the disruption of the mitochondrial respiratory chain lead to production of ROS that, in turn, induce lipid peroxidation and DNA damage, and result in defective spermatozoa up to induce sperm cytotoxicity. Investigating the effects of CuO NPs on sea urchin spermatozoa, this study provides valuable insights into the mechanism of reproductive toxicity induced by CuO NPs. Graphical abstract: Highlights: Spermiotoxicity of copper oxide nanoparticles (CuO NPs) in sea urchin Paracentrotus lividus . CuO NPs induce cytotoxicity, genotoxicity and morphological alterations in spermatozoa. CuO NPs induce reactive oxygen species generation, mitochondrial alteration and lipid peroxidation. Oxidative stress is the mechanism of CuO NP-induced reproductive toxicity.